THE CONTRIBUTION OF NEUROSCIENCES IN THE SENARIZATION OF LEARNING CONTENT AND EVALUATION STRATEGIES - Mazouak Abderrazzak; Rahhali Mohammed; Said Belaaouad (International Journal of Innovations in Engineering Research and Technology, 2022)
Since their appearance, neurosciences have allowed the definition and understanding of the brain activities that take place before, during and after new learning. And remain solid references for planning educational content on the one hand and improving teaching methods and appropriation strategies on the other. In the same perspective, the appearance of two opposing currents in the interval of neurosciences positioned teachers and educational actors before a dilemma between the supporters of the scientific authority of neurosciences to change certain teaching practices at a time when against opponents who warn against an abusive interpretation of images relating to learning activities. Our article will attempt in the first part to define the place of neurosciences in the educational sector and the learning process and then to explain the contribution of neurosciences on the practices of planning, management and evaluation of learning. without denying the set of limits of this contribution in the contribution of the improvement of the act of teaching-learning.